Willingness to contribute to the management of recreational quality on private lands in Finland - Lankia, Tuija; Neuvonen, Marjo; Pouta, Eija; Sievänen, Tuija (European Association of Agricultural Economists (EAAE), 2014)
In Finland, privately owned nature areas are widely used for recreation due to open public access. However, since landowners are not obligated to take everyman’s rights into consideration when making management decisions, the recreational quality of nature areas is not guaranteed for users. We examined whether individual recreationists on private lands would be willing purchase management actions from landowners that influence recreational quality. In addition to willingness to pay, we assessed willingness to con-tribute labor to such actions. The results demonstrated that about half of the recreationists who participated in our survey were willing to contribute labor and about 10% were willing to pay to direct the management of their typical recreation site on private lands. The mean willingness to pay was 92 euros per year and the mean willingness to contribute labor 3.5 days per year. A latent class regression model revealed that recreationists were not, however, completely homogeneous in their preferences for the actions or in their preferred contribution forms. On the basis of the results, there is moderate demand from recreationists for management to improve recreational quality and the potential for local landscape management arrangements that allow individual recreationists to contribute labor.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; payments of ecosystem services; recreation; willingness to pay; contingent valuation